Parenting and the development of effortful control from early childhood to early adolescence: A transactional developmental model. (18th July 2016) - Tiberio, Stacey S.; Capaldi, Deborah M.; Kerr, David C. R.; Bertrand, Maria; Pears, Katherine C.; Owen, Lee
Abstract: Poor effortful control is a key temperamental factor underlying behavioral problems. The bidirectional association of child effortful control with both positive parenting and negative discipline was examined from ages approximately 3 to 13–14 years, involving five time points, and using data from parents and children in the Oregon Youth Study—Three Generational Study ( N = 318 children from 150 families). Based on a dynamic developmental systems approach, it was hypothesized that there would be concurrent associations between parenting and child effortful control and bidirectional effects across time from each aspect of parenting to effortful control and from effortful control to each aspect of parenting. It was also hypothesized that associations would be more robust in early childhood, from ages 3 to 7 years, and would diminish as indicated by significantly weaker effects at the older ages, 11–12 to 13–14 years. Longitudinal feedback or mediated effects were also tested. The findings supported (a) stability in each construct over multiple developmental periods; (b) concurrent associations, which were significantly weaker at the older ages; (c) bidirectional effects, consistent with the interpretation that at younger ages children's effortful control influenced parenting, whereas at older child ages, parenting influenced effortful control; and (d) a transactional effect, such that maternal parenting in late childhood was a mechanism explaining children's development of effortful control from middle childhood to early adolescence.